1991
DOI: 10.1113/jphysiol.1991.sp018887
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic uptake of sulphur‐containing analogues of glutamate and aspartate by Müller cells from the salamander retina.

Abstract: SUMMARY1. The effect of sulphur-containing analogues of glutamate and aspartate on the membrane current of glial cells was studied by whole-cell clamping Muller cells isolated from the salamander retina.2. L-Cysteic acid (CA), L-cysteinesulphinic acid (CSA), L-homocysteic acid (HCA), L-homocysteinesulphinic acid (HCSA) and S-sulpho-L-cysteine (SC) all evoked an inward membrane current that was large at negative potentials, and was smaller (but did not reverse) at more positive potentials up to + 30 mV.3. Remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several of the amino acids examined in this study are endogenous to the CNS and have been previously evaluated as neurotrans- molpharm.aspetjournals.org mitter candidates at glutamatergic synapses. The candidature of sulfur-containing amino acids, which include L-Cys, HC, SSC, and HCSA, was considered after mechanisms that lead to their release, uptake, and responsiveness (see below) were identified (Do et al, 1986;Bouvier et al, 1991). Recent attention has focused on their potent activation of metabotropic glutamate receptors (e.g., Kingston et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several of the amino acids examined in this study are endogenous to the CNS and have been previously evaluated as neurotrans- molpharm.aspetjournals.org mitter candidates at glutamatergic synapses. The candidature of sulfur-containing amino acids, which include L-Cys, HC, SSC, and HCSA, was considered after mechanisms that lead to their release, uptake, and responsiveness (see below) were identified (Do et al, 1986;Bouvier et al, 1991). Recent attention has focused on their potent activation of metabotropic glutamate receptors (e.g., Kingston et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…1999). In addition to glutamate, these transporters also transport aspartate and several sulfur‐containing amino acids (Balcar and Johnston 1972; Bouvier et al . 1991; Schousboe and Westergaard 1995).…”
mentioning
confidence: 99%
“…Consequently, it could be argued that the HCA released from bipolar and amacrine cells and that possibly synthesized by Mi~ller cells, is accumulated in these glial cells. Under certain circumstances, HCA is released by a calcium-independent mechanism such as reversed operation of the electrogenic glutamate uptake or by exchange on the carrier with uptake of extracellular glutamate (Szatkowski et al, 1990;Bouvier et al, 1991). Finally, the accumulation of HCA in the extracellular space may lead to neuronal damage similar to that observed in the application of HCA to the chick retina and thus HCA may need to be actively removed by M~iller cells, and perhaps also by neurons.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, they remove K + from the extracellular space, metabolize carbon dioxide and also have uptake mechanisms for neurotransmitters (for reviews see Ripps & Witkovsky, 1985;Newman, 1986Newman, , 1987. In this sense, it has been shown that HCA is taken up into salamander M~iller cells by using the electrogenic glutamate transport mechanism, despite its low affinity for this Na +, K + and voltage dependent glutamate carrier (Bouvier et al, 1991). Consequently, it could be argued that the HCA released from bipolar and amacrine cells and that possibly synthesized by Mi~ller cells, is accumulated in these glial cells.…”
Section: Discussionmentioning
confidence: 97%